Clinical Entrepreneurship: A Student Teacher Assigning Desktop Documentary Making - James E. Schul (Research in Social Sciences and Technology- OpenED Network, 2017)
This study examines a student teacher's assignment of a historical documentary project in her middle school classroom placement. Results reveal that this student teacher and her cooperating teacher collaborated together to assign the project as a means to foster a personal connection with students and that their mutual commitment to this purpose fostered an experimentalist type of student teaching experience. Despite experiencing adversity with assigning the documentary project, the student teacher was not deterred from completing the project nor from her desire to assign a documentary making project in the future. Implications of these findings are discussed.